Comparison of the Effects of Two Oral Care Methods: A Pilot Study - Özlem, Dogu; Banu, Terzi (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Scrubbing with toothbrush and gargling with chlorhexidine has been shown to be effective in reducing bacteria and preventing ventilator-associated pneumonia (VAP) in patients in the intensive care unit (ICU). However, we still lack established evidencebased practice for oral care specific to ICUs. Objective: To evaluate effect of two oral care practices in two different ICUs as measured by the previously developed Intensive Care Oral Care Frequency Assessment Scale (ICOCFAS). Methods: This experimental pilot study was conducted with seven experiment group and seven control group of patients in the ICU setting.Data were collected using a patient information form, Richmond Sedation-Agitation Scale, Glasgow Coma Scale, pain score and ICOCFAS score. The research population consisted of inpatients in the ICU of a training and research hospital in Sakarya, Turkey. Results: After the application of two different oral care practices for seven days, there was no statistically significant difference between the groupsin before and after average total ICOCFAS scores, F(0.214, 14.570) =2.010 (p>0.05). However, when the group effect was kept constant, there was a significant difference between the measurements taken at the end of the seventh day,F(1.214, 14.570) =5.520 (p<0.05). Conclusion: Chlorhexidine combined with toothbrush scrubbing can reduce the incidence of ventilator-associated pneumonia (VAP). However, further studies are needed withlarger sample sizes and additional oral care plans for ICU patients on mechanical ventilation.ICU nurses should be continuously instructed on the importance of adequate dental biofilm removal, chlorhexidine solutions and toothbrush use. The ICOCFAS should be used to evaluate the oral care of patients in ICUs. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 412-419